Laparoscopic repair of voluminous symptomatic hiatal hernia using absorbable synthetic mesh. Issue 6 (2nd November 2015) - Berselli, Mattia; Livraghi, Lorenzo; Latham, Lorenzo; Farassino, Luca; Rota Bacchetta, Gian Luca; Pasqua, Noemi; Ceriani, Ileana; Segato, Sergio; Cocozza, Eugenio
Abstract: Introduction : Hiatal hernia is a common disorder and a controversial topic. In symptomatic voluminous hernias laparoscopic surgery and use of mesh can be considered. An initial experience in voluminous hiatal hernia laparoscopic repair using absorbable glycolic acid/trimethylene carbonate synthetic mesh is reported.Material and methods : Retrospective study from an institutional database was performed to analyze laparoscopic hiatal hernia repair using absorbable synthetic mesh from January 2010 to December 2013. All preoperative symptoms and exams were collected and a standardized procedure was performed. Clinical and radiological follow-up was performed.Results : Eight patients underwent laparoscopic repair of hiatal hernia performed by two highly skilled laparoscopic surgeons. One Toupet and seven Nissen fundoplications were tailored. No conversions into laparotomy, neither intraoperative complications nor mortality occurred. After a median follow-up of 23.5 months (range 14 - 44) no mesh complications occurred and all patients are asymptomatic. Two radiological recurrences (25%) were detected.Conclusions : Voluminous symptomatic hiatal hernias can be successfully treated in a high-volume and long-term experienced laparoscopic surgical center by the use of an absorbable synthetic mesh. Further studies and a longer-term follow-up are necessary to confirm this preliminary report.